2010
DOI: 10.1038/ejhg.2009.244
|View full text |Cite
|
Sign up to set email alerts
|

An unbalanced translocation unmasks a recessive mutation in the follicle-stimulating hormone receptor (FSHR) gene and causes FSH resistance

Abstract: Follicle-stimulating hormone (FSH) mediated by its receptor (FSHR) is pivotal for normal gametogenesis. Inactivating FSHR mutations are known to cause hypergonadotropic hypogonadism with disturbed follicular maturation in females. So far, only very few recessive point mutations have been described. We report on a 17-year-old female with primary amenorrhea, hypergonadotropic hypogonadism and disturbed folliculogenesis. Chromosome analysis detected a seemingly balanced translocation 46,XX,t(2;8)(p16.3or21;p23.1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…It has been previously reported that complete loss of FSHR function yields a block in follicular growth from the primary stage onward in female patients (Allen et al, 2003;Kuechler et al, 2010;Meduri et al, 2003), whereas a partial loss of function mutation might lead to normal follicular development up to the small antral stage and a disruption at later stages (Beau et al, 1998;Touraine et al, 1999). However, a recent study has shown that early antral follicles were observed in a female patient who was found to carry a homozygous FSHR mutation (p.Arg59Term) with complete loss of function in vitro (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that complete loss of FSHR function yields a block in follicular growth from the primary stage onward in female patients (Allen et al, 2003;Kuechler et al, 2010;Meduri et al, 2003), whereas a partial loss of function mutation might lead to normal follicular development up to the small antral stage and a disruption at later stages (Beau et al, 1998;Touraine et al, 1999). However, a recent study has shown that early antral follicles were observed in a female patient who was found to carry a homozygous FSHR mutation (p.Arg59Term) with complete loss of function in vitro (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ovaries showed a normal follicular development up to the small antral stage and a disruption at further stages. Primordial and intermediary follicles (few primary follicles) were observed Kuechler et al (2010) Minimum deletion in exons 9 and 10 and maximum deletion in exons 7-10 as FOXL2, NOBOX, LHX8, FOX10A, FOX03A, FIGLA, POU5F1, NANOS3, RASGRP3, KIT, (Qin et al 2012), which is not related to the FSHR gene located on chromosome 2. Existing paradigm in ovarian biology suggests that FSHR are expressed on the granulosa cells in ovaries and on the Sertoli cells in testes (Renner et al 2013, Siegel et al 2013.…”
Section: Referencesmentioning
confidence: 99%
“…Val were observed to lead to more adverse phenotypes such as primary amenorrhea (Achrekar et al 2010, Kuechler et al 2010). However, in vitro studies on the effect of the mutations in TMD on receptor trafficking have not yet been reported so far.…”
mentioning
confidence: 99%